Colonialist assumptions on colonial subjects and agents in Le Clézio’s novels (2021)
Stereotypes of the sub-Saharan African world, which were generateci by colonial French writers and denounced by their African counterparts, usually degraded thè Blacks to justify colonialism. This paper focuses on the representations of the colonised Africans in Onitsha, South-East Nigeria, in novels written by Le Ciàzio, a French writer. Postcolonial literary theory is applied to explore the experiences of representations and ‘othering’ in relation to the Western hegemonic discourse and Fanon ’s dichotomy between thè coloniser and the colonised. The study establishes colonialists’ assumptions permeating Le Ciàzio ’s Onitsha, L ’Africain and Chercheur d'or. Sub-Saharan Africa is debased as an undeveloped and dirty land, with Africans dehumanised and infantilized as subaltems, redundant, bestiai, superstitious and cannibalistic people. Also, their virtues are negated and trivialised by Europeans, who, conversely portray themselves as better and superior people, compassionate about the plight of Africans and willing to bring to Africa the knowledge and benefits of Western civilisation. These debasing representations of sub-Saharan Africans in Onitsha as the inferi or Other’ of the European ‘Self foreground the writer’s intention to accept how colonial mentality, a result of hegemonic western discourse ,influences his fellow Europeans.